2013
DOI: 10.1021/ma401667d
|View full text |Cite
|
Sign up to set email alerts
|

The Controlled Polymerization of Poly(cyclopentadithiophene)s and Their All-Conjugated Block Copolymers

Abstract: Abstract. In this manuscript, the Kumada catalyst transfer polymerization (KCTP) of cyclopenta [2,1-b;3,4-b']dithiophene (CPDT), a monomer consisting of two fused thiophene entities, is investigated. It is shown that this polymerization follows a controlled chain-growth mechanism. Furthermore, the formation of block-copolymers with poly(3-alkylthiophene)s is investigated, and it is shown that these block-copolymers can be formed if 3-alkylthiophene is used as the first block and CPDT as the second. The resulti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

4
37
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
3
2
1

Relationship

1
5

Authors

Journals

citations
Cited by 41 publications
(41 citation statements)
references
References 78 publications
4
37
0
Order By: Relevance
“…Even though the mechanism was discovered and developed for P3AT, it was rapidly applied to several other conjugated polymers. Presently several conjugated polymers can be synthesized by KCTCP, such as poly( p ‐phenylene), poly(3‐alkylselenophene), poly( N ‐alkylpyrrole), poly(4‐alkylthiazole), poly(dithienosilole), poly(cyclopentadithiophene), poly(bithienylmethylene), and poly(fluorenes) . In 2008, Ohshimizu et al showed that the polymerization of poly(2,4‐dialkoxy‐ m ‐phenylene) using KCTCP is living.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations
“…Even though the mechanism was discovered and developed for P3AT, it was rapidly applied to several other conjugated polymers. Presently several conjugated polymers can be synthesized by KCTCP, such as poly( p ‐phenylene), poly(3‐alkylselenophene), poly( N ‐alkylpyrrole), poly(4‐alkylthiazole), poly(dithienosilole), poly(cyclopentadithiophene), poly(bithienylmethylene), and poly(fluorenes) . In 2008, Ohshimizu et al showed that the polymerization of poly(2,4‐dialkoxy‐ m ‐phenylene) using KCTCP is living.…”
Section: Introductionmentioning
confidence: 99%
“…It was also found that an alkoxy‐sidechain in the ortho ‐position hampers oxidative insertion due to its strong electron‐donating effect . Also, poly(fluorene)s, poly(cyclopentadithiophene)s, and poly(dithienosilole)s can all be polymerized in a living fashion, proving ortho ‐substituents are not necessary …”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…15). This synthetic method, now known as catalyst transfer polycondensation (CTP) (13)(14)(15)(16)(17)(18)(19), paved the way for synthesizing all-conjugated diblock copolymers (20)(21)(22)(23)(24)(25)(26)(27), star polymers (28,29) and surface-grafted polymers (30)(31)(32). CTP also provides access to all-conjugated gradient sequence copolymers (33)(34)(35)(36).…”
Section: Introductionmentioning
confidence: 99%